Ответы и объяснения

Лучший Ответ!
2013-12-07T17:26:25+04:00
 \frac{( \frac{ y^{2} + 9 }{27 + 3 y^{2} } +  \frac{y}{3y + 9} -  \frac{3}{ y^{2} - 3y } )}{ \frac{ (3y + 9)^{2} }{3 y^{2} -  y^{3}  } } =   \frac{( \frac{(y + 3) ^{2} }{3(y + 3) ^{2} } +  \frac{y}{3(y + 3)} -  \frac{3}{y(y - 3)})}{ \frac{3(y + 3) ^{2} }{y ^{2}(3 - y) } } =  - \frac{\frac{y(y + 3) ^{2}(y - 3) + y ^{2}(y - 3)(y + 3) - 9(y + 3) ^{2}   }{3y(y - 3)(y + 3) ^{2} } }{ \frac{3(3-y)}{ y^{2} } } == - \frac{3y }{(y + 3) ^{2} } :   \frac{3(3 - y)}{y ^{2} } =  \frac{y ^{3} }{(y ^{2} - 9)(y + 3) } = \frac{y ^{3} }{y ^{3} - 6y - 27 }
Не до конца уверен, но вроде должно быть верно
После третьего и перед четвертым должно стоять равно.